Effects of calorie restriction on the zebrafish liver proteome - Jury, David R. (2008)
A proteomic approach was taken to study how fish respond to changes in calorie availability, with the longer-term goal of understanding the evolution of lipid metabolism in vertebrates. Zebrafish (Danio rerio) were fed either high (3 rations/day) or low (1 ration/7 days) calorie diets for 5 weeks and liver proteins extracted for proteomic analyses. Proteins were separated on two-dimensional electrophoresis gels and homologous spots compared between treatments to determine which proteins were up-regulated with high-calorie diet. Fifty-five spots were excised from the gel and analyzed via LC–ESI MS/MS, which resulted in the identification of 69 unique proteins (via multiple peptides). Twenty-nine of these proteins were differentially expressed between treatments. Differentially expressed proteins were mapped to Gene Ontology (GO) terms, and these terms compared to the entire zebrafish GO annotation set by Fisher's exact test. The most significant GO terms associated with high-calorie diet are related to a decrease in oxygen-binding activity in the high-calorie treatment. This response is consistent with a well-characterized response in obese humans, indicating there may be a link between lipid storage and hypoxia sensitivity in vertebrates.